Profil kemampuan pemecahan masalah mahasiswa calon guru fisika pada mata kuliah Kapita Selekta Fisika Sekolah II melalui problem based learning - Duwi Nuvitalia; Ernawati Saptaningrum (Perkumpulan Kualitama Edukatika Indonesia, 2020)
Learning does not only prioritize results because it needs a process so that learning becomes more meaningful. The meaningfulness of a material can be reached in various ways. One of them is learning Physics which is not only concerned with theory but also needs a strategy to be able to solve the problems in it. Thus, Physics can be comprehensively understood by students who learn it. Students as prospective teachers are expected to be able to study physics thoroughly, one of which is through problem-based learning in order to have problem-solving abilities. The purpose of this study was to determine the profile description of the problem-solving ability of prospective physics teacher students in the Kapita Selekta School Physics II course through problem-based learning. This research is a descriptive method with a qualitative approach. Data collection techniques in this study were carried out through the analysis of written documentation from research subjects and structured interviews regarding the information on students' ability in problem-solving through problem-based learning. Based on the results of the discussion, it was concluded that the profile of the problem-solving ability of prospective physics teacher students in the Kapita Selecta School Physics Course II through Problem Based Learning was in a good category with an average of 73.91%. In accordance with the curriculum policy in learning that one of the competencies of students must be able to solve problems.